Candidemia in major burns patients. Issue 6 (2nd March 2016) - Renau Escrig, Ana I.; Salavert, Miguel; Vivó, Carmen; Cantón, Emilia; Pérez del Caz, M. Dolores; Pemán, Javier
Summary: Major burn patients have characteristics that make them especially susceptible to candidemia, but few studies focused on this have been published. The objectives were to evaluate the epidemiological, microbiological and clinical aspects of candidemia in major burn patients, determining factors associated with a poorer prognosis and mortality. We conducted a retrospective observational study of candidemia between 1996 and 2012 in major burn patients admitted to the La Fe University Hospital, Valencia, Spain. The study included 36 episodes of candidemia in the same number of patients, 55.6% men, mean age 37.33 years and low associated comorbidity. The incidence of candidemia varied between 0.26 and 6.09 episodes/1000 days stay in the different years studied. Candida albicans was the most common species (61.1%) followed by Candida parapsilosis (27.8%). Candidemia by C. krusei, C. glabrata or C. tropicalis were all identified after 2004. Central vascular catheter (CVC) was established as a potential source of candidemia in 36.1%, followed by skin and soft tissues of thermal injury (22.2%) and urinary tract (8.3%). Fluconazole was used in 19 patients (52.7%) and its in vitro resistance rate was 13.9%. The overall mortality was 47.2%, and mortality related to candidemia was 30.6%. Factors associated with increased mortality were those related to severe infection and shock. CVC was the most usual focus of candidemia. Fluconazole was the most common antifungal drug administered. The management of candidemia in major burn patients is still a challenge.